THE IMBRICATION OFPUBLIC ANDPRIVATE DIMENSIONS IN WOMEN'S WORK - Wilza Rocha Pereira (Universidade Federal do Paraná, 1998)
A qualitative study was conducted to examine some aspects of the work nurses and of women's work in its public and private dimensions. Nine nursing professors who simultaneousíy teach and provide care in a public institution were interviewed. The data were analyzed against the theoretical background of social relations concerning gender. We concluded that there is a profound relationship between the public and privte dimensions in the type of work investigated.